Nonaqueous electrolyte storage element and method for producing same
By incorporating a fluorinated solvent in the nonaqueous electrolyte and using a separator with low air permeability resistance in nonaqueous electrolyte storage devices with metallic lithium negative electrodes, the growth of dendrites and subsequent short circuits are suppressed, ensuring high capacity retention and device reliability.
Patent Information
- Application Number
- JP2021567294
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-23
- Filing Date
- 2020-12-15
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2040-12-15
AI Technical Summary
Nonaqueous electrolyte storage devices using metallic lithium as the negative electrode active material are prone to short circuits due to dendrite growth, which penetrates the separator and contacts the positive electrode.
A nonaqueous electrolyte storage element is designed with a negative electrode of metallic lithium, a nonaqueous electrolyte containing a fluorinated solvent, and a separator with an air permeability resistance of 150 seconds or less, which suppresses dendrite growth and short circuits.
The proposed solution effectively suppresses the occurrence of short circuits and maintains a high capacity retention rate during charge and discharge cycles, enhancing the reliability and performance of nonaqueous electrolyte storage devices.
Smart Images

Figure 0007658279000006 
Figure 0007658279000007 
Figure 0007658279000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a non-aqueous electrolyte electricity storage element and a method for producing the same. [Background technology]
[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. The non-aqueous electrolyte secondary batteries generally have a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring ions between the electrodes. In addition, as non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used. Metallic lithium is known as a negative electrode active material having a high energy density and used in non-aqueous electrolyte storage elements (see Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2016-100065 A [Patent Document 2] Japanese Patent Application Publication No. 07-245099 Summary of the Invention [Problem to be solved by the invention]
[0004] In a nonaqueous electrolyte storage device in which metallic lithium is used as the negative electrode active material, metallic lithium may precipitate in dendritic form on the surface of the negative electrode during charging (hereafter referred to as "dendrite"); When the dendrite grows and penetrates the separator and contacts the positive electrode, it causes a short circuit. Therefore, nonaqueous electrolyte storage elements having metal lithium as the negative electrode active material have the disadvantage that short circuits are likely to occur due to repeated charge and discharge.
[0005] The present invention has been made in light of the above-mentioned circumstances, and an object of the present invention is to provide a nonaqueous electrolyte storage element in which the occurrence of short circuits is suppressed, and a method for manufacturing such a nonaqueous electrolyte storage element. [Means for solving the problem]
[0006] One embodiment of the present invention is a nonaqueous electrolyte electricity storage element including a negative electrode having metallic lithium, a nonaqueous electrolyte containing a fluorinated solvent, and a separator having an air resistance of 150 seconds or less.
[0007] Another aspect of the present invention is a method for producing a nonaqueous electrolyte storage element, the method including: preparing a negative electrode having metallic lithium; preparing a nonaqueous electrolyte containing a fluorinated solvent; and preparing a separator having an air resistance of 150 seconds or less. Effect of the Invention
[0008] Advantageous Effects of Invention According to one aspect of the present invention, it is possible to provide a nonaqueous electrolyte electricity storage element in which the occurrence of short circuits is suppressed, and a method for manufacturing such a nonaqueous electrolyte electricity storage element. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is an external perspective view showing a nonaqueous electrolyte electricity storage element according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an electricity storage device formed by assembling a plurality of nonaqueous electrolyte electricity storage elements according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] First, an outline of the nonaqueous electrolyte storage element and the method for producing the nonaqueous electrolyte storage element disclosed in this specification will be described.
[0011] A nonaqueous electrolyte storage element according to one embodiment of the present invention is a nonaqueous electrolyte storage element including a negative electrode having metallic lithium, a nonaqueous electrolyte containing a fluorinated solvent, and a separator having an air resistance of 150 seconds or less.
[0012] The nonaqueous electrolyte storage element prevents the occurrence of short circuits. The reason for this is unclear, but the following reasons are speculated: By using a separator with low air permeability resistance, the concentration distribution of lithium ions in the nonaqueous electrolyte near the surface of the negative electrode is uniform, thereby suppressing dendrite precipitation and growth. Furthermore, the film formed on the negative electrode surface by a nonaqueous electrolyte containing a fluorinated solvent suppresses the deposition and growth of dendrites. Therefore, it is presumed that using a nonaqueous electrolyte containing a fluorinated solvent and a separator with an air permeability resistance of 150 seconds or less will suppress the growth of dendrites and the occurrence of short circuits. Furthermore, the nonaqueous electrolyte storage element suppresses the occurrence of short circuits, and therefore the capacity retention rate during charge and discharge cycles is also high.
[0013] Here, the "air permeability resistance" is a value measured by the "Gurley tester method" in accordance with JIS-P8117 (2009). The dimensions of the separator test piece used for the measurement are 50 mm x 50 mm. The air permeability resistance of the separator included in the nonaqueous electrolyte storage element is measured using a separator obtained from the nonaqueous electrolyte storage element dismantled by the following method. First, after the nonaqueous electrolyte storage element is discharged, the nonaqueous electrolyte storage element is disassembled in a dry atmosphere. Next, the separator is removed, washed with hydrochloric acid having a concentration of 36% by mass, and then further washed with deionized water, and then vacuum dried at room temperature for more than 10 hours. After that, the vacuum-dried separator is cut out to form a test piece.
[0014] The negative electrode provided in the nonaqueous electrolyte storage element requires as long as it has metal lithium at least in its charging state, and may or may not have metal lithium in its discharge state. For example, it may be a nonaqueous electrolyte storage element in which metal lithium is deposited in at least a part of the negative electrode surface in the charging state, and substantially all of the metal lithium on the negative electrode surface is eluted in the nonaqueous electrolyte by discharge, and in the discharge state, metal lithium is substantially no longer present on the anode surface in the discharging state.
[0015] The air resistance is preferably from 50 seconds to 80 seconds. By using a separator with such an air resistance, the occurrence of short circuits in the nonaqueous electrolyte storage element is further suppressed.
[0016] It is preferred that the separator includes a base resin and inorganic particles dispersed in the base resin. By using such a separator, the occurrence of short circuits in the nonaqueous electrolyte storage element is further suppressed. Although the reason for this effect is not clear, it is presumed that the separator has a suitable porous shape due to the presence of inorganic particles, and that the separator has a high strength due to the presence of inorganic particles, and that the separator has a suitable porous shape can be maintained even when the separator is pressurized, and that good high permeability is maintained.
[0017] The positive electrode potential at the end of charge voltage during normal use of the nonaqueous electrolyte storage element is 4.30 V vs. Li / Li + By setting the positive electrode potential at the end of charge voltage during normal use to the above lower limit or higher, the discharge capacity can be increased and the energy density can be increased. + When the above-mentioned charge and discharge is repeated to reach a high potential, it is thought that the amount of electricity used to decompose components of the nonaqueous electrolyte with low oxidation resistance at the positive electrode is used for the deposition and growth of dendrite at the negative electrode, and short circuits are likely to occur. Therefore, the advantages of the present invention that eliminate such disadvantages can be fully enjoyed.
[0018] The manufacturing method of a nonaqueous electrolyte storage device according to one aspect of the present invention is a method of manufacturing a nonaqueous electrolyte storage device comprising preparing a combination of a positive electrode and a negative electrode having a metallic lithium or a negative electrode having a surface region where metallic lithium can be deposited upon charging, preparing a nonaqueous electrolyte containing a fluorinated solvent, and preparing a separator having an air permeability resistance of 150 seconds or less.
[0019] According to this manufacturing method, a nonaqueous electrolyte electricity storage element in which the occurrence of short circuits is suppressed can be manufactured.
[0020] Hereinafter, a nonaqueous electrolyte electricity storage element according to one embodiment of the present invention and a method for producing the nonaqueous electrolyte electricity storage element will be described in order.
[0021] <Non-aqueous electrolyte electricity storage element> The nonaqueous electrolyte storage element according to one embodiment of the present invention has a positive electrode, a negative electrode and a nonaqueous electrolyte. Below, a nonaqueous electrolyte secondary battery (hereinafter also referred to simply as a "secondary battery") will be described as an example of a nonaqueous electrolyte storage element. The positive and negative electrodes are usually formed by stacking or winding an electrode body alternately superimposed via a separator. The electrode body is housed in a container, and the container is filled with a nonaqueous electrolyte. The nonaqueous electrolyte is interposed between the positive electrode and the negative electrode. Furthermore, the above-mentioned container may be a known metal container, a resin container, or the like, normally used as a container for a secondary battery.
[0022] (positive electrode) The positive electrode has a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer.
[0023] The positive electrode substrate has electrical conductivity. "Conductivity" means that the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 7 "Non-conductive" means that the volume resistivity is 10 7This means that it is greater than Ω·cm. The material of the positive electrode substrate is a metal such as aluminum, titanium, tantalum, stainless steel, or an alloy thereof. Of these, aluminum and aluminum alloys are preferred because of the balance between potential resistance, high conductivity and cost. Furthermore, as a form of forming the positive electrode substrate, foils and vapor deposition films can be cited, and foils are preferred from the viewpoint of cost. In other words, aluminum foil is preferred as the positive electrode substrate. As the aluminum or aluminum alloy, A1085P, A3003P, etc., as defined in JIS-H-4000 (2014).
[0024] The average thickness of the positive electrode substrate is preferably 3 μm or more and 50 μm or less, more preferably 5 μm or more and 40 μm or less, even more preferably 8 μm or more and 30 μm or less, and particularly preferably 10 μm or more and 25 μm or less. By setting the average thickness of the positive electrode substrate within the above range, it is possible to increase the strength of the positive electrode substrate while increasing the energy density per volume of the secondary battery. The "average thickness" refers to the value obtained by dividing the punched mass when a substrate of a predetermined area is punched out by the true density and punched area of the substrate. The same applies to the "average thickness" of the negative electrode substrate and the negative electrode active material layer described below.
[0025] The intermediate layer is a coating layer on the surface of the positive electrode substrate, and contains conductive particles such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. The configuration of the intermediate layer is not particularly limited, and can be formed, for example, from a composition containing a resin binder and conductive particles.
[0026] The positive electrode active material layer is a layer formed from a so-called positive electrode mixture containing a positive electrode active material. The positive electrode mixture forming the positive electrode active material layer may contain optional components such as a conductive agent, a binder, a thickener, and a filler as necessary.
[0027] The positive electrode active material can be appropriately selected from known positive electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the positive electrode active material for a lithium ion secondary battery. Examples of the positive electrode active material include lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel type crystal structure, polyanion compounds, chalcogen compounds, and sulfur. Examples of the lithium transition metal composite oxides having an α-NaFeO2 type crystal structure include Li[Li x Ni 1-x ]O2(0≦x<0.5), Li[Li x Ni γ Co 1-x-γ ]O2(0≦x<0.5, 0<γ<1), Li[Li x Co 1-x ]O2(0≦x<0.5), Li[Li x Ni γ Mn 1-x-γ ]O2(0≦x<0.5, 0<γ<1), Li[Li x Ni γ Mn β Co 1-x-γ-β ]O2(0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), Li[Li x Ni γ Co β Al 1-x-γ-β ]O2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), etc. Lithium transition metal composite oxides with spinel crystal structure include Li x Mn2O4, Li x Ni γ Mn 2-γO4, etc. Examples of polyanion compounds include LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. Examples of chalcogen compounds include titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. Atoms or polyanions in these materials may be partially substituted with atoms or anion species of other elements. The surfaces of these materials may be coated with other materials. In the positive electrode active material layer, one of these materials may be used alone, or two or more may be mixed and used.
[0028] The average particle size of the positive electrode active material is preferably, for example, 0.1 μm or more and 20 μm or less. By setting the average particle size of the positive electrode active material to the above lower limit or more, the positive electrode active material can be easily manufactured or handled. By setting the average particle size of the positive electrode active material to the above upper limit or less, the electronic conductivity of the positive electrode active material layer is improved. Here, the "average particle size" refers to a value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50% based on the particle size distribution measured by a laser diffraction / scattering method for a diluted solution obtained by diluting particles with a solvent in accordance with JIS-Z-8825 (2013).
[0029] In order to obtain particles of the positive electrode active material in a predetermined shape, a pulverizer, a classifier, etc. are used. As a pulverization method, for example, a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve, etc. can be used. When pulverizing, wet pulverization in which water or an organic solvent such as hexane is coexistent can also be used. As a classification method, a sieve, a wind classifier, etc. are used as necessary for both dry and wet methods.
[0030] The content of the positive electrode active material in the positive electrode active material layer is preferably 70% by mass to 98% by mass, more preferably 80% by mass to 97% by mass, and even more preferably 90% by mass to 96% by mass. By setting the content of the positive electrode active material in the above range, the electric capacity of the secondary battery can be increased.
[0031] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include carbonaceous materials, metals, and conductive ceramics. Examples of carbonaceous materials include graphite and carbon black. Examples of carbon black include furnace black, acetylene black, and ketjen black. Among these, carbonaceous materials are preferred from the viewpoint of electrical conductivity and coating properties. Among these, acetylene black and ketjen black are preferred. Examples of the shape of the conductive agent include powder, sheet, and fiber.
[0032] The content of the conductive agent in the positive electrode active material layer is preferably from 1% by mass to 40% by mass, more preferably from 2% by mass to 10% by mass. By setting the content of the conductive agent in the above range, the energy density of the secondary battery can be increased.
[0033] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, and polyimide; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), and fluororubber; and polysaccharide polymers.
[0034] The content of the binder in the positive electrode active material layer is preferably 0.5% by mass to 10% by mass, more preferably 1% by mass to 6% by mass. By setting the content of the binder in the above range, the active material can be stably held.
[0035] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. In addition, when the thickener has a functional group that reacts with lithium, it is preferable to deactivate this functional group in advance by methylation or the like. In one embodiment of the present invention, it may be preferable that the thickener is not contained in the positive electrode active material layer.
[0036] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, aluminum oxide, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and artificial products thereof. In one embodiment of the present invention, it may be preferable that the filler is not contained in the positive electrode active material layer.
[0037] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.
[0038] (Negative electrode) The negative electrode has a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The intermediate layer of the negative electrode may have the same structure as the intermediate layer of the positive electrode.
[0039] The negative electrode substrate can have the same structure as the positive electrode substrate, but the material is a metal such as copper, nickel, stainless steel, nickel-plated steel, or an alloy thereof, and copper or a copper alloy is preferred. That is, the negative electrode substrate is preferably a copper foil. Examples of the copper foil include rolled copper foil and electrolytic copper foil.
[0040] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate within the above range, it is possible to increase the strength of the negative electrode substrate and to increase the energy density per volume of the secondary battery.
[0041] The negative electrode active material layer contains metallic lithium. The metallic lithium is a component that functions as a negative electrode active material. The metallic lithium may exist as pure metallic lithium substantially consisting of lithium alone, or may exist as a lithium alloy containing other metal components. Examples of the lithium alloy include a lithium silver alloy, a lithium zinc alloy, a lithium calcium alloy, a lithium aluminum alloy, a lithium magnesium alloy, and a lithium indium alloy. The lithium alloy may contain a plurality of metal elements other than lithium.
[0042] The negative electrode active material layer may be a layer consisting essentially of metallic lithium. The lithium content in the negative electrode active material layer may be 90% by mass or more, may be 99% by mass or more, or may be 100% by mass.
[0043] The negative electrode active material layer may be a lithium foil or a lithium alloy foil. The negative electrode active material layer may be a non-porous layer (solid layer). The negative electrode active material layer may also be a porous layer having particles containing metallic lithium. The negative electrode active material layer, which is a porous layer having particles containing metallic lithium, may further contain, for example, resin particles, inorganic particles, etc. The average thickness of the negative electrode active material layer is preferably 5 μm or more and 1,000 μm or less, more preferably 10 μm or more and 500 μm or less, and even more preferably 30 μm or more and 300 μm or less.
[0044] In the case of a nonaqueous electrolyte storage element configured such that metallic lithium is precipitated on at least a portion of the negative electrode surface in a charged state and substantially all of the metallic lithium on the negative electrode surface is dissolved into the nonaqueous electrolyte upon discharging, the negative electrode does not need to have a negative electrode active material layer in a discharged state.
[0045] (Separator) The separator is not particularly limited as long as it has an air resistance of 150 seconds or less, and can be appropriately selected from known separators. For example, a separator consisting of only a base layer, a separator in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both sides of the base layer, etc. can be used as the separator. From the viewpoint of further suppressing the occurrence of a short circuit, a separator consisting of only a base layer may be preferable.
[0046] Examples of the form of the substrate layer of the separator include woven fabric, nonwoven fabric, and porous resin film, with porous resin film being preferred. The material of the substrate layer of the separator is usually a resin. As the resin (substrate resin) that is the material of the substrate layer of the separator, polyolefins such as polyethylene and polypropylene are preferred from the viewpoint of shutdown function, and polyimide and aramid are preferred from the viewpoint of oxidation and decomposition resistance. A composite material of these resins may be used as the substrate layer of the separator.
[0047] The separator preferably has a base resin and inorganic particles dispersed in the base resin. By using a separator in which inorganic particles are dispersed in the base resin, the occurrence of short circuits in the nonaqueous electrolyte storage element is further suppressed. In a separator having a base resin and inorganic particles dispersed in the base resin, a base layer is usually formed by the base resin and the inorganic particles. In this case, it is more preferable that the separator is a separator consisting of only a base layer, that is, a separator without other layers such as a heat-resistant layer. In addition, by containing inorganic particles dispersed in the base layer of the separator, the separator can have good heat resistance even in the absence of a heat-resistant layer. The base layer may further contain other components other than the base resin and the inorganic particles.
[0048] Specific types of base resin include the resins mentioned above as the material for the base layer of the separator.
[0049] Specific types of materials constituting the inorganic particles include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, barium titanate, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; poorly soluble ion crystals such as calcium fluoride and barium fluoride; covalent crystals such as silicon and diamond; mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof. As the inorganic compound, a single substance or a complex of these substances may be used alone, or two or more types may be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferable from the viewpoint of safety of the nonaqueous electrolyte storage element.
[0050] The content of inorganic particles in the base layer is preferably 1% by mass or more and 70% by mass or less, more preferably 5% by mass or more and 50% by mass or less, and even more preferably 10% by mass or more and 20% by mass or less. By having the content of inorganic particles in the above range, the occurrence of short circuits in the nonaqueous electrolyte storage element is further suppressed. In addition, by having the content of inorganic particles in the above range, the balance between strength (pressure resistance in the thickness direction), flexibility, resistance to tearing, etc. is optimized.
[0051] The heat-resistant particles contained in the heat-resistant layer preferably have a mass loss of 5% or less when heated from room temperature to 500°C in the atmosphere, and more preferably have a mass loss of 5% or less when heated from room temperature to 800°C in the atmosphere. Examples of materials that have a mass loss of a predetermined amount or less when heated include inorganic compounds. Examples of inorganic compounds include those mentioned above as materials constituting the inorganic particles in the base layer. Among inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate are preferred from the viewpoint of safety of the nonaqueous electrolyte storage element.
[0052] The air resistance of the separator is preferably 30 seconds or more and 150 seconds or less, more preferably 35 seconds or more and 100 seconds or less, and even more preferably 50 seconds or more and 80 seconds or less. By using a separator having an air resistance in the above range, the occurrence of a short circuit in the nonaqueous electrolyte storage element is further suppressed. The air resistance of the separator is adjusted by the porosity, average thickness, etc. of the separator. In addition, a commercially available product can be used as a separator having such an air resistance.
[0053] The average thickness of the separator is preferably, for example, 3 μm or more and 50 μm or less, and more preferably 10 μm or more and 25 μm or less. When the average thickness of the separator is equal to or more than the lower limit, the occurrence of a short circuit can be further suppressed. On the other hand, when the average thickness of the separator is equal to or less than the upper limit, the energy density of the nonaqueous electrolyte storage element can be increased. The average thickness of the separator is the average value of thicknesses measured at any 10 points.
[0054] (Non-aqueous electrolyte) The non-aqueous electrolyte includes a fluorinated solvent. The non-aqueous electrolyte may be a non-aqueous electrolytic solution including a non-aqueous solvent including a fluorinated solvent and an electrolyte salt dissolved in the non-aqueous solvent.
[0055] The fluorinated solvent is a solvent having fluorine atoms. The fluorinated solvent may be a non-aqueous solvent having a hydrocarbon group, in which some or all of the hydrogen atoms in the hydrocarbon group are substituted with fluorine atoms. The non-aqueous electrolyte contains a fluorinated solvent, thereby suppressing the occurrence of short circuit. In addition, the use of a fluorinated solvent increases oxidation resistance, and good charge-discharge cycle performance can be maintained even during charging in which the positive electrode potential during normal use reaches a high potential. Examples of the fluorinated solvent include fluorinated carbonates, fluorinated carboxylates, fluorinated phosphates, and fluorinated ethers. One or more fluorinated solvents can be used.
[0056] Among the fluorinated solvents, fluorinated carbonates are preferred, and it is more preferred to use a combination of a fluorinated cyclic carbonate and a fluorinated chain carbonate. By using a fluorinated cyclic carbonate, dissociation of the electrolyte salt can be promoted to improve the ionic conductivity of the non-aqueous electrolyte. By using a fluorinated chain carbonate, the viscosity of the non-aqueous electrolyte can be kept low. When a fluorinated cyclic carbonate and a fluorinated chain carbonate are used in combination, the volume ratio of the fluorinated cyclic carbonate to the fluorinated chain carbonate (fluorinated cyclic carbonate:fluorinated chain carbonate) is preferably in the range of, for example, 5:95 to 50:50.
[0057] The lower limit of the content of the fluorinated carbonate in the fluorinated solvent is preferably 50% by volume, more preferably 70% by volume, and further preferably 90% by volume. The upper limit of the content of the fluorinated carbonate in the fluorinated solvent may be 100% by volume.
[0058] Examples of the fluorinated cyclic carbonate include fluoroethylene carbonate (FEC), fluorinated ethylene carbonate such as difluoroethylene carbonate, fluorinated propylene carbonate, and fluorinated butylene carbonate. Among these, fluorinated ethylene carbonate is preferred, and FEC is more preferred. FEC has high oxidation resistance and is highly effective in suppressing side reactions (such as oxidative decomposition of non-aqueous solvents) that may occur during charging and discharging of secondary batteries.
[0059] Examples of the fluorinated chain carbonate include trifluoromethylethyl carbonate, trifluoroethylmethyl carbonate, bis(trifluoromethyl)carbonate, and bis(trifluoroethyl)carbonate.
[0060] Examples of the fluorinated carboxylate include methyl 3,3,3-trifluoropropionate and 2,2,2-trifluoroethyl acetate.
[0061] Examples of the fluorinated phosphate ester include tris(2,2-difluoroethyl) phosphate and tris(2,2,2-trifluoroethyl) phosphate.
[0062] Examples of fluorinated ethers include 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, methyl heptafluoropropyl ether, and methyl nonafluorobutyl ether.
[0063] The non-aqueous solvent may contain a non-aqueous solvent other than the fluorinated solvent, such as carbonates, carboxylates, phosphates, ethers, etc., other than the fluorinated solvent.
[0064] The lower limit of the content of the fluorinated solvent in the total nonaqueous solvent is preferably 50% by volume, more preferably 70% by volume, and even more preferably 90% by volume. By increasing the content of the fluorinated solvent in the nonaqueous solvent, it is possible to further improve short-circuit suppression properties, oxidation resistance, etc.
[0065] The electrolyte salt can be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, onium salts, etc. Among these, lithium salts are preferred.
[0066] Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, and lithium salts having a halogenated hydrocarbon group such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.
[0067] The content of the electrolyte salt in the non-aqueous electrolyte is 0.1 mol / dm 3 More than 2.5mol / dm 3 It is preferable that the value is 0.3 mol / dm or less. 3More than 2.0mol / dm 3 More preferably, it is 0.5 mol / dm or less. 3 More than 1.7mol / dm 3 More preferably, it is 0.7 mol / dm or less. 3 More than 1.5mol / dm 3 By setting the content of the electrolyte salt within the above range, the ionic conductivity of the non-aqueous electrolyte can be increased.
[0068] The non-aqueous electrolyte may contain an additive. Examples of the additive include aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, t-butylbenzene, t-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the above aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, cyclohexyl benzene, and cyclohexyl benzene. hexanedicarboxylic anhydride; ethylene sulfite, propylene sulfite, dimethyl sulfite, dimethyl sulfate, ethylene sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, dipyridinium disulfide, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsilyl titanate, etc. These additives may be used alone or in combination of two or more.
[0069] The content of the additive in the non-aqueous electrolyte is preferably 0.01% by mass to 10% by mass, more preferably 0.1% by mass to 7% by mass, even more preferably 0.2% by mass to 5% by mass, and particularly preferably 0.3% by mass to 3% by mass. By setting the content of the additive in the above range, it is possible to improve the capacity retention performance or the charge / discharge cycle performance after high-temperature storage, and to further improve safety.
[0070] In this secondary battery (non-aqueous electrolyte storage element), the positive electrode potential at the end of charge voltage during normal use is 4.30 V vs. Li / Li + It is preferable that the value is 4.35V vs. Li / Li or more. + More preferably, it is 4.40V vs. Li / Li or more. + By setting the positive electrode potential at the end-of-charge voltage during normal use to the above lower limit or higher, it is possible to increase the discharge capacity and the energy density.
[0071] In addition, "normal use" refers to a case where the nonaqueous electrolyte storage element is used under charging conditions recommended or specified for the nonaqueous electrolyte storage element. For example, if a charger for the nonaqueous electrolyte storage element is provided, the "normal use" refers to a case where the nonaqueous electrolyte storage element is used using the charger.
[0072] The upper limit of the positive electrode potential at the end of charge voltage during normal use of the secondary battery is, for example, 5.0 V vs. Li / Li + 4.8V vs. Li / Li + 4.7V vs. Li / Li + It may be.
[0073] In the nonaqueous electrolyte storage element, it is preferable that at least a part of the electrode body composed of the positive electrode, the negative electrode, and the separator is in a pressurized state. Such pressurization tends to increase the capacity retention rate during repeated charging and discharging. For example, the electrode body housed in a container may be pressurized from the outside of the container, i.e., through the container. It is preferable that the electrode body is pressurized in the direction in which the positive electrode, the negative electrode, and the separator are stacked (thickness direction of each layer). That is, it is preferable that the positive electrode active material layer and the negative electrode active material layer are pressurized in the direction in which they are crushed in the thickness direction. However, a part of the electrode body (for example, a pair of curved surface parts in a flat wound electrode body) may not be pressurized. In addition, only a part of the flat part of a laminated electrode body and a flat wound electrode body may be pressurized. The pressure applied to at least a part of the electrode body in the pressurized state or the pressure applied to the container from the outside is preferably 0.01 MPa or more and 2 MPa or less, more preferably 0.1 MPa or more and 1.5 MPa or less, and even more preferably 0.2 MPa or more and 1 MPa or less. By setting the pressure to be equal to or higher than the lower limit, the capacity retention rate can be increased sufficiently, whereas by setting the pressure to be equal to or lower than the upper limit, the occurrence of short circuits during repeated charging and discharging can be further suppressed.
[0074] The electrode body can be pressurized, for example, by a pressurizing member that pressurizes the container from the outside. The pressurizing member may be a restraining member that restrains the shape of the container. The pressurizing member (restraining member) is provided so as to pressurize the electrode body from both sides in the thickness direction, for example, via the container. The surface of the electrode body that is pressurized is in contact with the inner surface of the container directly or via another member. Therefore, the electrode body is pressurized by pressurizing the container. Examples of the pressurizing member include a restraining band and a metal frame. For example, the metal frame may be configured so that the load can be adjusted by a bolt or the like. In addition, a plurality of nonaqueous electrolyte storage elements may be arranged in the thickness direction of the electrode body, and fixed using a frame or the like in a state in which the plurality of nonaqueous electrolyte storage elements are pressurized from both ends in the thickness direction.
[0075] Dendrites tend to grow easily when the current density during charging is high. Therefore, the nonaqueous electrolyte storage element according to one embodiment of the present invention can be suitably applied to applications in which charging is performed at a high current density. Examples of such applications include power sources for automobiles such as electric vehicles (EVs), hybrid vehicles (HEVs), and plug-in hybrid vehicles (PHEVs), power sources for aircraft such as airplanes and drones, and power sources for charging with regenerative power. Among these, the nonaqueous electrolyte storage element is particularly suitable for use as a power source for aircraft because it combines an extremely high mass energy density, which is particularly required for a power source for an aircraft, with sufficient charge and discharge cycle performance.
[0076] The shape of the nonaqueous electrolyte storage element of this embodiment is not particularly limited, and examples thereof include a cylindrical battery, a prismatic battery, a flat battery, a coin battery, and a button battery.
[0077] Fig. 1 shows a nonaqueous electrolyte storage element 1 as an example of a prismatic battery. The figure is a see-through view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a prismatic container 3. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51.
[0078] <Configuration of Nonaqueous Electrolyte Electricity Storage Device> The nonaqueous electrolyte storage element of the present embodiment can be mounted as an electricity storage unit (battery module) comprising a plurality of nonaqueous electrolyte storage elements assembled together in automobile power sources such as electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc., aircraft power sources such as airplanes and drones, power sources for electronic devices such as personal computers and communication terminals, or power storage power sources, etc. In this case, the technology according to one embodiment of the present invention may be applied to at least one nonaqueous electrolyte storage element included in the electricity storage unit.
[0079] 2 shows an example of an electricity storage device 30 in which electricity storage units 20, each of which is an assembly of two or more electrically connected nonaqueous electrolyte electricity storage elements 1, are further assembled. The electricity storage device 30 may include a bus bar (not shown) that electrically connects two or more nonaqueous electrolyte electricity storage elements 1, a bus bar (not shown) that electrically connects two or more electricity storage units 20, and the like. The electricity storage unit 20 or the electricity storage device 30 may include a status monitoring device (not shown) that monitors the status of one or more nonaqueous electrolyte electricity storage elements.
[0080] <Method of Manufacturing Nonaqueous Electrolyte Storage Element> A method for producing a nonaqueous electrolyte storage element according to one embodiment of the present invention includes preparing a combination of a positive electrode and a negative electrode having metallic lithium or a negative electrode having a surface region on which metallic lithium can be deposited during charging, preparing a nonaqueous electrolyte containing a fluorinated solvent, and preparing a separator having an air resistance of 150 seconds or less.
[0081] The preparation of the negative electrode having metallic lithium may be the preparation of a negative electrode having metallic lithium. The negative electrode can be prepared by laminating a negative electrode active material layer containing metallic lithium directly or via an intermediate layer on a negative electrode substrate, and pressing the layer. The negative electrode active material layer containing metallic lithium may be a lithium foil or a lithium alloy foil. The specific and preferred forms of the prepared negative electrode can be the forms described above as the negative electrode provided in the nonaqueous electrolyte storage element.
[0082] The negative electrode having a surface region on which metallic lithium can be deposited during charging may be, for example, a negative electrode made only of a negative electrode substrate. When preparing a negative electrode having a surface region on which metallic lithium can be deposited during charging, a positive electrode having a positive electrode active material containing lithium ions is prepared in advance.
[0083] The preparation of the nonaqueous electrolyte containing a fluorinated solvent may be the preparation of a nonaqueous electrolyte containing a fluorinated solvent. The preparation of the nonaqueous electrolyte can be performed by mixing each component constituting the nonaqueous electrolyte, such as the fluorinated solvent and other components. The specific and preferred forms of the prepared nonaqueous electrolyte can be the forms described above for the nonaqueous electrolyte provided in the nonaqueous electrolyte storage element.
[0084] The preparation of a separator having an air resistance of 150 seconds or less may be performed by preparing or purchasing a commercially available product of such a separator, or by manufacturing such a separator. The specific and preferred forms of the separator to be prepared are the forms described above for the separator provided in the nonaqueous electrolyte storage element.
[0085] For example, a method for producing the nonaqueous electrolyte storage element includes preparing or producing a positive electrode, preparing or producing a negative electrode, preparing or preparing a nonaqueous electrolyte, preparing or producing a separator, laminating or winding the positive electrode and the negative electrode with the separator interposed therebetween to form an electrode assembly in which the positive electrode and the negative electrode (electrode assembly) are alternately stacked, housing the positive electrode and the negative electrode (electrode assembly) in a container, and injecting the nonaqueous electrolyte into the container. After injection, the injection port is sealed to obtain the nonaqueous electrolyte storage element.
[0086] <Other embodiments> The present invention is not limited to the above-described embodiments, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.
[0087] In the above embodiment, the nonaqueous electrolyte storage element is used as a chargeable and dischargeable nonaqueous electrolyte secondary battery (e.g., a lithium ion secondary battery), but the type, shape, size, capacity, etc. of the nonaqueous electrolyte storage element are arbitrary. The nonaqueous electrolyte storage element of the present invention can also be applied to various nonaqueous electrolyte secondary batteries, electric double layer capacitors, lithium ion capacitors, and other capacitors. EXAMPLES
[0088] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0089] The separators used in the examples and comparative examples are shown below. The base resins used were all produced by biaxial stretching. Separator A: Air resistance 35 seconds, average thickness 16 μm, separator (without heat-resistant layer) consisting of a base layer having inorganic particles dispersed in the base resin (polyolefin resin), content of inorganic particles in the base layer 50% by mass Separator B: Air resistance 45 seconds, average thickness 16 μm, separator (without heat-resistant layer) consisting of a base layer having inorganic particles dispersed in the base resin (polyolefin resin), content of inorganic particles in the base layer 25% by mass Separator C: Air resistance 70 seconds, average thickness 16 μm, separator (without heat-resistant layer) consisting of a base layer having inorganic particles dispersed in the base resin (polyolefin resin), content of inorganic particles in the base layer 15% by mass Separator D: Air resistance 90 seconds, average thickness 21 μm, separator consisting of a base layer made only of base resin (polyolefin resin) and a heat-resistant layer Separator E: Air resistance 172 seconds, average thickness 17 μm, separator consisting of a base layer made only of base resin (polyolefin resin) and a heat-resistant layer. Separator F: Air resistance 286 seconds, average thickness 25 μm, separator consisting of a base layer made only of base resin (polyolefin resin) Separator G: Air resistance 300 seconds, average thickness 24 μm, separator consisting of a base layer made only of base resin (polyolefin resin) and a heat-resistant layer.
[0090] [Example 1] (Preparation of positive electrode) The positive electrode active material has an α-NaFeO2 type crystal structure and Li 1+α Me 1-α A lithium transition metal composite oxide represented by O2 (Me is a transition metal) was used. Here, the molar ratio of Li to Me, Li / Me, was 1.33, and Me was composed of Ni and Mn, and was contained in a molar ratio of Ni:Mn=1:2.
[0091] A positive electrode paste was prepared containing the positive electrode active material, acetylene black (AB) as a conductive agent, and polyvinylidene fluoride (PVDF) as a binder in a mass ratio of 94:4.5:1.5, using N-methylpyrrolidone (NMP) as a dispersion medium. The positive electrode paste was applied to one side of an aluminum foil having an average thickness of 15 μm as a positive electrode substrate, dried, pressed, and then cut to prepare a positive electrode having a positive electrode active material layer arranged in a rectangular shape of 30 mm wide and 40 mm long.
[0092] (Preparation of negative electrode) A lithium foil (100% by mass of metallic lithium) with an average thickness of 100 μm was laminated as a negative electrode active material layer on one side of a copper foil with an average thickness of 10 μm, which served as a negative electrode substrate. After pressing, the laminate was cut into a rectangular shape with a width of 32 mm and a length of 40 mm to prepare a negative electrode.
[0093] (Preparation of non-aqueous electrolyte) Fluoroethylene carbonate (FEC) and 2,2,2-trifluoroethyl methyl carbonate (TFEMC) were mixed in a volume ratio of 30:70, and LiPF6 was added at 1 mol / dm 3 to give a non-aqueous electrolyte.
[0094] (Preparation of non-aqueous electrolyte storage element) An electrode body was produced by stacking the positive electrode and the negative electrode via the separator A. This electrode body was housed in a container, the nonaqueous electrolyte was poured into the inside, and the container was sealed and pressurized from the outside at 0.3 MPa to produce a nonaqueous electrolyte storage element (secondary battery) of Example 1.
[0095] [Examples 2 to 4 and Comparative Examples 1 to 5] Non-aqueous electrolyte storage elements of Examples 2 to 4 and Comparative Examples 1 to 5 were obtained in the same manner as in Example 1, except that the type of separator and the composition of the non-aqueous solvent of the non-aqueous electrolyte were as shown in Table 1. In the table, EC stands for ethylene carbonate, and EMC stands for ethyl methyl carbonate.
[0096] (Initial charge / discharge) The obtained nonaqueous electrolyte storage elements were initially charged and discharged under the following conditions. At 25°C, constant current and constant voltage charging was performed with a charge amount of 0.1C and a charge end voltage of 4.60V. The charge end condition was that the charge current was 0.02C. Then, a rest period of 10 minutes was provided. Then, constant current discharging was performed with a discharge current of 0.1C and a discharge end voltage of 2.00V, and then a rest period of 10 minutes was provided. This charge and discharge cycle was performed for two cycles.
[0097] (Charge-discharge cycle test) Next, the following charge-discharge cycle test was performed. At 25°C, constant current and constant voltage charging was performed with a charging current of 1C and a charge cut-off voltage of 4.60V. The charge was terminated until the charging current reached 0.05C. A rest period of 10 minutes was then provided. Then, constant current discharging was performed with a discharging current of 1C and a discharge cut-off voltage of 2.00V, followed by a rest period of 10 minutes. This charge-discharge cycle was repeated, and the number of cycles until a short circuit occurred was recorded. For those in which the number of cycles until a short circuit occurred exceeded 25, the discharge capacity retention rate was calculated. The discharge capacity retention rate was defined as the discharge capacity at the 25th cycle relative to the discharge capacity at the 5th cycle. The results are shown in Table 1.
[0098] [Table 1]
[0099] As shown in Table 1, in Comparative Example 1 and Comparative Example 5 using a non-aqueous electrolyte containing no fluorinated solvent, and Comparative Examples 2 to 5 using a separator with an air permeability resistance of more than 150 seconds, a short circuit occurred after a small number of cycles of less than 20. In contrast, in the non-aqueous electrolyte storage elements of Examples 1 to 4 using a non-aqueous electrolyte containing a fluorinated solvent and a separator with an air permeability resistance of 150 seconds or less, the number of cycles until a short circuit occurred exceeded 40, the occurrence of a short circuit was sufficiently suppressed, and the discharge capacity retention rate was also high. Among them, the non-aqueous electrolyte storage element of Example 3 showed a result in which the occurrence of a short circuit was particularly suppressed, possibly because the air permeability resistance of the separator was particularly appropriate. [Industrial Applicability]
[0100] The present invention can be applied to nonaqueous electrolyte electricity storage elements used as power sources for electronic devices such as personal computers and communication terminals, and automobiles. [Explanation of symbols]
[0101] 1. Non-aqueous electrolyte storage element 2 Electrode body 3 containers 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Energy Storage Unit 30 Energy storage device
Claims
1. a negative electrode having a negative electrode active material layer containing metallic lithium; a non-aqueous electrolyte comprising a fluorinated solvent; and A separator having an air resistance of 150 seconds or less Equipped with A nonaqueous electrolyte storage element, wherein the content of the metallic lithium in the negative electrode active material layer is 90 mass % or more.
2. A negative electrode having metallic lithium; A non-aqueous electrolyte comprising a non-aqueous solvent containing a fluorinated solvent; and A separator having an air resistance of 150 seconds or less Equipped with A nonaqueous electrolyte storage element in which the content of the fluorinated solvent relative to the total amount of the nonaqueous solvent is 50% by volume or more (excluding the case where the nonaqueous electrolyte contains one or more compounds selected from a fluorinated ether represented by the following formula (1) and a fluorinated phosphate ester represented by the following formula (2), and the separator contains an aramid resin: 【Chemistry 1】 [In formula (1), R 4 and R 5 each independently represent an alkyl group or a fluorinated alkyl group. At least one of R 4 and R 5 is a fluorinated alkyl group.] 【Chemistry 2】 [In formula (2), R 6 , R 7 and R 8 each independently represent a substituted or unsubstituted alkyl group, and at least one of R 6 , R 7 and R 8 is a fluorinated alkyl group. The carbon atom of R 6 and the carbon atom of R 7 may be bonded via a single bond or a double bond to form a cyclic structure.]
3. 3. The nonaqueous electrolyte storage element according to claim 1, wherein the air resistance is from 50 seconds to 80 seconds.
4. 4. The nonaqueous electrolyte storage element according to claim 1, wherein the separator comprises a base resin and inorganic particles dispersed in the base resin.
5. The positive electrode potential at the end of charge voltage during normal use is 4.30 V (vs. Li / Li + 5. The nonaqueous electrolyte storage element according to claim 1, wherein the content of the nonaqueous electrolyte is 1 or more.
6. Preparing a combination of a positive electrode and a negative electrode having a negative electrode active material layer containing metallic lithium or a negative electrode having a surface region on which metallic lithium can be deposited during charging; Providing a non-aqueous electrolyte comprising a fluorinated solvent; and Prepare a separator having an air resistance of 150 seconds or less. Equipped with The method for producing a nonaqueous electrolyte storage element, wherein the content of the metallic lithium in the negative electrode active material layer is 90 mass % or more.
7. Preparing a combination of a positive electrode and a negative electrode having metallic lithium or a negative electrode having a surface region on which metallic lithium can be deposited during charging; Providing a non-aqueous electrolyte comprising a non-aqueous solvent containing a fluorinated solvent; and Prepare a separator having an air resistance of 150 seconds or less. Equipped with A method for producing a nonaqueous electrolyte storage element, in which a content ratio of the fluorinated solvent to the total amount of the nonaqueous solvent is 50% by volume or more (excluding the case where the nonaqueous electrolyte contains one or more compounds selected from a fluorinated ether represented by the following formula (1) and a fluorinated phosphate ester represented by the following formula (2), and the separator contains an aramid resin: 【Chemistry 3】 [In formula (1), R 4 and R 5 each independently represent an alkyl group or a fluorinated alkyl group. At least one of R 4 and R 5 is a fluorinated alkyl group.] 【Chemistry 4】 [In formula (2), R 6 , R 7 and R 8 each independently represent a substituted or unsubstituted alkyl group, and at least one of R 6 , R 7 and R 8 is a fluorinated alkyl group. The carbon atom of R 6 and the carbon atom of R 7 may be bonded via a single bond or a double bond to form a cyclic structure.]
Citation Information
Patent Citations
Negative electrode for nonaqueous electrolyte type lithium secondary battery
JP1995245099A
Lithium ion secondary battery
JP2012064569A
Power storage device
JP2013055285A
Nonaqueous electrolyte and power storage device including the same, and power storage apparatus having power storage device
JP2016095965A
Lithium secondary battery
JP2016100065A